High performance liquid chromatographic method for quantitation of apigenin from dried root powder of Gmelina arborea Linn - SHREEDA ADHYAPAK; Dr. VIDYA DIGHE; DHANASHRI MESTRY; NEETA SHAMBHU (International Journal of Pharma and Bio Sciences, 2011)
A simple fast and precise reverse phase high performance liquid chromatographic method is developed for the quantitative determination of apigenin, a flavonoid from dried root powder of Gmelina arborea Linn. Apigenin was extracted from root powder of Gmelina arborea Linn. by using warm methanol as the extracting solvent. The quantization of apigenin was carried out on an Inertsil ODS-3V-C18, (25cm x 4.6 mm i.d., 5µm) column, using acetonitrile and distilled water in volume ratio of (45:55), as the mobile phase. The detection of the standard was carried out at 340 nm, using UV-Visible detector, which is reported to be the wavelength of maximum absorption of the standard apigenin.The proposed HPLC method was validated and applied for the quantitative determination of apigenin from Gemlina arborea Linn